2019
DOI: 10.3389/fneur.2019.01262
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of Amyloidogenic Blood Clotting in the Evolving Haemodynamics of Female Migraine-With-Aura: Results From a Pilot Study

Abstract: Introduction: Migraine is a debilitating primary headache disorder with a poorly understood aetiology. An extensive body of literature supports the theory of migraine as a systemic vascular inflammatory disorder characterised by endothelial dysfunction. It is also well-known that chronic inflammation results in an excessive burden of oxidative stress and therefore cellular dysfunction. In this study the effects of excessive oxidative stress through the phases of female migraine-with-aura (FMA) were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…In our current research, it comes as no surprise that serum ferritin levels are increased in COVID-19 blood samples, as it is known as a marker of damaged cells [31]. Its presence in the circulation may cause pathology to platelet erythrocytes, as well as the plasma protein fibrinogen [18][19][20][21][22][23][32][33][34][35][36][37][38]. Iron can also leak into the circulation due to cellular damage to not only erythrocytes but, also, endothelial and other cells.…”
Section: Discussionmentioning
confidence: 83%
“…In our current research, it comes as no surprise that serum ferritin levels are increased in COVID-19 blood samples, as it is known as a marker of damaged cells [31]. Its presence in the circulation may cause pathology to platelet erythrocytes, as well as the plasma protein fibrinogen [18][19][20][21][22][23][32][33][34][35][36][37][38]. Iron can also leak into the circulation due to cellular damage to not only erythrocytes but, also, endothelial and other cells.…”
Section: Discussionmentioning
confidence: 83%
“…It is apparent that our investigation into the structural properties of fibrin networks in RA and its relation to hemostatic function has a rather deceptive appearance. Our group has previously shown that fibrin networks in multiple inflammatory conditions (113,(121)(122)(123) and in plasma exposed to inflammatory stimuli (26,114,124) stain positive for amyloid-specific dyes. This constitutes the appearance of misfolded, protein aggregates with enriched β -sheet content that confers a higher degree of insolubility (125).…”
Section: Discussionmentioning
confidence: 99%
“…Strongly bound up with the coagulopathies accompanying severe COVID-19 disease is the presence of hyperferritinaemia (in cases such as the present it is a cell damage marker (28)) and a cytokine storm, (29)(30)(31)(32)(33) which usually occurs in the later phase of the disease (16). Excess iron has long been known to cause blood to clot into an anomalous form (34), later shown to be amyloid in nature (18)(19)(20)(21)(22)(23)(24). These kinds of phenomena seem to accompany essentially every kind of inflammatory disease (e.g.…”
Section: Discussionmentioning
confidence: 99%